Politics and economics in the Russian Far East : changing ties with Asia-Pacific - Akaha, Tsuneo, 1949- (Routledge, 1997)
This extremely thorough and broad-ranging study analyses the complex issues involved in the development of co-operative economic relationships between Russia and its Asia-Pacific neighbours.